2018
DOI: 10.1073/pnas.1812266115
|View full text |Cite
|
Sign up to set email alerts
|

Blocking IL-1β reverses the immunosuppression in mouse breast cancer and synergizes with anti–PD-1 for tumor abrogation

Abstract: Interleukin-1β (IL-1β) is abundant in the tumor microenvironment, where this cytokine can promote tumor growth, but also antitumor activities. We studied IL-1β during early tumor progression using a model of orthotopically introduced 4T1 breast cancer cells. Whereas there is tumor progression and spontaneous metastasis in wild-type (WT) mice, in IL-1β–deficient mice, tumors begin to grow but subsequently regress. This change is due to recruitment and differentiation of inflammatory monocytes in the tumor micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
299
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(322 citation statements)
references
References 74 publications
19
299
2
2
Order By: Relevance
“…We found that uric acid stimulates TNF-alpha production, but not IL-1 beta, in a dose-dependent fashion after confirming that human monocytes were properly differentiated into macrophages using a strategy that combined cell size and complexity as well CD14 expression. TNF-alpha and IL-1 beta are proinflammatory cytokines that play key roles in fever, cachexia, tumorigenesis inhibition, pyroptosis-related cell death, and immune cell recruitment [24][25][26]. However, TNF-alpha, but not IL-1 beta, has been consistently associated with increased serum levels of uric acid in several pathologic scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…We found that uric acid stimulates TNF-alpha production, but not IL-1 beta, in a dose-dependent fashion after confirming that human monocytes were properly differentiated into macrophages using a strategy that combined cell size and complexity as well CD14 expression. TNF-alpha and IL-1 beta are proinflammatory cytokines that play key roles in fever, cachexia, tumorigenesis inhibition, pyroptosis-related cell death, and immune cell recruitment [24][25][26]. However, TNF-alpha, but not IL-1 beta, has been consistently associated with increased serum levels of uric acid in several pathologic scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1-mediated tumor promotion has been identified in different murine and human tumor types, including sarcomas, melanoma, pancreatic ductal adenocarcinoma (Ling et al, 2012;Melisi et al, 2009;Tjomsland et al, 2013;Zhuang et al, 2016), myelomas (Lust et al, 2016), and breast carcinomas and involves different mechanisms ( Figure 4A). IL-1 has been shown to sustain the expansion and immunosuppressive function of myeloid cells in tumor-bearing mice (Elkabets et al, 2010;Kaplanov et al, 2019;Pan et al, 2017).…”
Section: Il-1 Family Members In Cancer Progressionmentioning
confidence: 99%
“…We leveraged these distinct gene expression signatures associate with suppression of the antitumor immune response to identify drug candidates that could be repurposed for cancer immunotherapy. Although, IL-1 is a prototypical pro-inflammatory cytokine, recent studies suggest that IL-1β can drive tumorigenesis by promoting a CSC phenotype, modulating the immune response and inducing tumorigenic edema [39][40][41][42] . Importantly, randomized clinical testing of canakinumab, an anti-IL-1β antibody, pointed out to a reduction in lung cancer incidence of patients with atherosclerosis 43 .…”
Section: Discussionmentioning
confidence: 99%